PENGARUH BIAYA OPERASIONAL TERHADAP LABA BERSIH PADA BANK SWASTA NASIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2011 - Fadhillah Ramadhani Nasution; Lisa Marlina (Universitas Sumatera Utara, 2013)
Abstract This research entitled “The Effect of Operating Expenses on Net Profit of National Private Bank Listed in Indonesia Stock Exchange Period of Year 2009-2011”. The purpose of this research is to investigate and analyze the effect of interest expenses, general administration cost, and labor cost on net profit of national private bank listed in Indonesia Stock Exchange. The research method uses descriptive analysis method and statistic analysis method. This research uses secondary data, there were 20 companies. Hypothesis testing is done by using F test and T test, with significance level (α) 5%. The results of the simultaneous hypothesis test indicate that the variable interest expenses, general administration cost, and labor cost influence on net profit. The results of the partial hypothesis test indicate that the variable interest expenses has an influence on net profit but variable general administration cost and labor cost hasn’t influence on net profit. Keywords: Interest Expenses, General Administration Cost, Labor Cost, and Net Profit